RESPONS PEMBERIAN PUPUK ORGANIK CAIR (POC) DAUN KELOR PADA JENIS MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa L.) - PRATIWI, EIS SUKMAWATI; KARIMUNA, LA; SUBAIR, IMRAN; RAHNI, NINI MILA; ARSYAD, MIRZA ARSIATY; MADIKI, ABDUL (Jurnal Agroteknos, 2023)
This study aimed to determine the response of growth and yield of lettuce (Lactuca sativa L). This research was carried out at the Field Laboratory of Experimental Gardens II and the Laboratory of Agrotechnology, Faculty of Agriculture, Halu Oleo University from December 2021 to February 2022. This research was carried out using a Randomized Block Design (RBD) with a single factor consisting of five treatment levels, namely, No Organic Fertilizer Liquid (P0), Liquid Organic Fertilizer 10 ml.L-1 (P1), Liquid Organic Fertilizer 20 ml.L-1 (P2), Liquid Organic Fertilizer 30 ml.L-1 (P3), Liquid Organic Fertilizer 40 ml. L-1 (P4) and each treatment was repeated three times, each replication contained 15 plants, so the total treatment unit was 45 polybags. The variables observed were: plant height (cm), number of leaves (strands), leaf area (cm2), wet weight of plants (g), dry weight of plants (g), wet weight of plant roots (g), and dry weight of plant roots. Each observation variable was analyzed using analysis of variance to determine the effect of treatment. if there is F-count greater than F-table followed by UJBD at a 95% confidence level. The results showed that the liquid organic fertilizer treatment had an effect on the observed variables of plant roots at harvest, which showed that at (10 ml.L-1) is the best concentration by showing the highest average value of lettuce plant growth and yield